Abbreviations. - Murray, Kara (Murray, Kara. Core language skills., 2014)
We live in a fast-paced world. Time is tighter than ever, and we're always looking for shortcuts-even in writing! Language students will learn all about abbreviations: why we use them, how we use them, and when and where they're appropriate. The text covers a variety of abbreviations, from date and time to places and names. Internet and texting abbreviations are covered, too, but with a friendly reminder of when they should be used. This title features a quiz question on every spread, with answers found at the end of the book. Fun graphic organizers and eye-catching images round out the text,